"Foundations of Linguistic Reform and Its Civilizational Dimension in the Works of Imam Muhammad al-Bashir al-Ibrahimi" - daraoucha, omar (El Omda in Linguistics and Discourse Analysis, 2018)
This study seeks to examine the foundations of linguistic reform and its civilizational dimension in the works of Imam al-Ibrahimi, by discussing the Imam and his linguistic achievements, and by uncovering the efforts and principles of linguistic reform reflected in his personality. It also aims to highlight the civilizational dimensions of al-Ibrahimi’s service to the Arabic language, as well as its development and advancement in light of the transformations witnessed in Arab and Islamic societies. The study concludes with a section presenting the findings and recommendations, followed by research notes and a list of sources and references.